Β‐Catenin mediates tumor‐induced immunosuppression by inhibiting cross‐priming of CD8+ T cells. Issue 1 (10th September 2013) - Liang, Xinjun; Fu, Chunmei; Cui, Weiguo; Ober‐Blöbaum, Julia L.; Zahner, Sonja P.; Shrikant, Protul A.; Clausen, Björn E.; Flavell, Richard A.; Mellman, Ira; Jiang, Aimin
Abstract : Tumors activate β‐catenin in DCs to suppress CD8 immunity by inhibiting cross‐priming; β‐catenin‐suppressed CD8 immunity could be rescued by enhancing cross‐priming. Abstract : Whereas CD8 + T cells are essential for anti‐tumor immunity, tumors often evade CD8 + T cell surveillance by immunosuppression. As the initiators of antigen‐specific immune responses, DCs are likely to play a central role in regulating the balance between immunity and tolerance to tumor antigens and are specialized in their ability to cross‐present exogenous tumor antigens on MHC class I molecules to initiate CD8 + T cell immunity. However, it remains unclear whether and how tumors modulate DC functions to suppress CD8 + T cell responses. We have shown previously that β‐catenin signaling in DCs promotes DC‐mediated CD4 + T cell tolerance. Here, we tested the hypothesis that β‐catenin in DCs mediates tumor‐induced suppression of CD8 + T cell immunity by inhibiting the ability of DCs in cross‐priming. β‐Catenin was activated in DCs by multiple tumors in vivo and in vitro. B16 melanoma‐bearing mice, when vaccinated with DC‐targeting anti‐DEC‐205 mAb fused with tumor antigens, exhibited dampened CD8 + immunity, similar to DC‐β‐catenin active mice. DCs from DC‐β‐catenin active and tumor‐bearing mice were deficient in cross‐priming, and antigen‐specific CD8 + T cells primed in these mice resulted in dampened CD8 + memory responses. Importantly, DC‐β‐catenin −/− mice completely abrogate tumor‐mediated inhibition of cross‐priming, suggesting that tumor‐induced inhibition of cross‐priming is dependent on β‐catenin. Finally, enhancing cross‐priming at the priming or recall phase rescued β‐catenin‐suppressed CD8 + immunity in DC‐β‐catenin active and tumor‐bearing mice. Thus, β‐catenin‐mediated inhibition of cross‐priming represents a new and potentially general mechanism that tumors employ to achieve immunosuppression.